Economic analysis and efficiency in policing, criminal justice and crime reduction : what works? /: what works?. (2016) - Manning, Matthew; Johnson, Shane D, 1971-; Tilley, Nick; Wong, Gabriel T. W; Vorsina, Margarita
No abstract available